The Unity and the Struggle of Didactics and Autodidactics - Albena Velcheva (Педагогически форум)
The article describes the development of didactics and auto-didactics using the diachronic approach. The relation between didactics, as a major and traditional part of pedagogical science, and autodidactics, as its variety and alternative, is presented in the context of the law of unity and struggle of opposites, which is the "core" of dialectics. The validity of the general laws of dialectics and their relation to pedagogical science is argued. From a philosophical and pedagogical point of view, the basic principles are formulated, arising from the interdependence and contradiction in the didactics-autodidactics system as factors for the sustainable development of education.